Pengaruh Pengetahuan Literasi Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Hotel di Kabupaten Boyolali - Naomi Anjani Saktyaningrum; Hadi Samanto; Darmanto, Darmanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of tax literacy knowledge, taxpayer awareness, and tax sanctions on hotel taxpayer compliance in Boyolali Regency. The research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 58 respondents who are hotel taxpayers in Boyolali Regency. The data were analyzed using multiple linear regression analysis. The results show that tax literacy knowledge has a positive influence on taxpayer compliance with a significance value of 0.001. Taxpayer awareness also has a positive influence on taxpayer compliance with a significance value of 0.000. Additionally, tax sanctions have a positive influence on taxpayer compliance with a significance value of 0.006. Based on these results, it can be concluded that all three independent variables significantly affect the level of hotel taxpayer compliance in Boyolali Regency.